Peruvian Banking Financial Performance 2007–2017 - Emmerich, Lourdes (2020)
DOI: https://doi.org/10.26439/ing.ind2020.n038.4818 The financial performance of Peruvian banks from 2007 to 2017 has shown high banking concentration, solvency, profitability and liquidity. This research analyzes variables such as capital, assets, management, profitability and liquidity. The improvement opportunities in Peruvian banks are focused on financial inclusion and economies of scale, in view of volatility and vulnerability risks to climate phenomena and political corruption.